Slovenes in Neighbouring Countries as Part of the Curriculum in Primary and Secondary Schools in Slovenia - Čok, Lucija (Revija za elementarno izobraževanje, 2021)
Slovenes live as an autochthonous minority in neighbouring countries of Italy, Austria, Hungary and Croatia. The common European space allows them to develop a cultural area with far-reaching implications. An analytical review of Slovenian minorities through the content of curricula of primary and secondary schools examined the presence of topics related to them. Researchers that analysed the school curricula and textbooks with a special questionnaire for pupils, students and general population assessed the current situation in school practice. Following the processing of quantitative data and consultation meetings with experts changes and additions to the curricula of primary and secondary schools were proposed.